The Horse : A Natural History - Busby, Debbie, 1960-; Rutland, Catrin (Book collections on Project MUSE., 2019)
A comprehensive, richly illustrated introduction to the fascinating natural history of the horse, from prehistory to the presentThere are countless books about keeping and riding horses. The Horse is different: it looks not only at the natural history of the horse in the context of its use by humans, but also at its own, independent story, describing the way horses live, think, and behave both alongside people and on their own. Beautifully designed and illustrated, The Horse provides an engaging and accessible introduction to these beloved animals. Beginning with evolution and development, The Horse tells how horses came into being more than fifty million years ago and were first domesticated more than five thousand years ago, eventually spreading across the globe. Chapters on Anatomy & Biology and Society & Behavior explain equine anatomy and how it has affected the lives and social structure of horses, and outline current scientific thinking on their behavior, both as individual and herd animals, including information on communication between horses. A chapter on Horses & People provides a thorough overview of the horse's many important roles in human history and today, from pack animal to sporting champion. Finally, the book ends with an engrossing and visually stunning photographic gallery of some fifty popular breeds of horses and ponies with essential information about each. Filled with surprising facts and insights, this book will delight anyone who loves horses and wants to understand them better. Provides a comprehensive, richly illustrated introduction to the evolution, development, domestication, and behavior of the horse--from life cycle, breeding, coats and colors, and the senses to courtship, parenting, communication, emotions, and learningTells the full story of horses, from their earliest fossil ancestors to the modern-day EquusOffers a detailed survey of how horses and humans have interacted since horses were domesticated, including their use for work and war in the past and recreational and competitive riding todayFeatures infographics, diagrams, and more than 250 stunning color photographsIncludes a beautiful photographic directory to some 50 popular breeds.